Fluorescent carbon-dots thin film for fungal detection and bio-labeling applications - Gaikwad, Aarti; Joshi, Meenal; Patil, Kashinath; Sathaye, Shivaram; Rode, Chandrashekhar V. (ACS Applied Bio Materials, 2019)
The fluorescence properties of CDs, such as high quantum yield, tunability of emission color, and so on, make a strong potential material in various fields. These applications are mainly derived from in situ formation of surface functional groups, high chemical stability, biocompatibility, and easy interaction with substrates, etc. Mostly, the research applications of CDs concentrate on the labeling of biological species, drug delivery, and sensing in consequent biomedical applications. However, the detection of the fungal species/spores present in the environment by using CDs is rarely reported. Herein, we demonstrate CDs-based thin film as a sensor for detection of fungal spores from the environment. The procedure of detection is based on fluorescence, observed in the film of carbon dots deposited on quartz plates by using the Blodgett technique. It is observed that the CDs film shows quenching in the fluorescence intensity by the substrate, namely, fungal spores’ (Aspergillus niger, Penicillium chrysogenum, Alternaria alternata). The effective features of the present detector system are easy fabrication, low cost, high stability, and a green and economical procedure of synthesis. The process of detecting fungal spores even at low concentration from the atmosphere is relatively fast when compared to presently used methods. Finally, real-world feasibility of the sensor film is tested by its successful application for the determination of the presence fungal spores in the environment. Furthermore, CDs have been also successfully applied for the bio-labeling of Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) bacterial systems.